Modeling of electromigration induced contact resistance reduction of Cu-Cu bonded interface - Made, Riko I. (2012)
Metal to metal bonding, particularly Cu-Cu bonding, is an important part of three dimensional integrated circuits (3DICs) that utilizes wafer bonding. The use of Cu to Cu bonding in 3DICs is advantageous as it functions as both the glue layer and electrical interconnection. It has been observed that the contact resistance of bonded Cu interface could be decreased under direct current stressing. In this paper the mentioned phenomena is modeled and simulated. Electromigration induced contact resistance reduction of bonded interconnects may provide a method for post-bonding bond property improvement for 3DICs